STRATEGI TIM P4GN DALAM PENCEGAHAN PEMBERANTASAN PENYALAHGUNAAN DAN PEREDARAN GELAP NARKOBA BERBASIS MASYARAKAT DI KABUPATEN SUKOHARJO - PRABOWO, BRIAN PRIMANDA (Dinamika Hukum, 2018)
The purpose of this research are to know and analyze : 1) to know and analyze the strategy and implementation of P4GN team in the prevention of the eradication of using and illicit traffic of the drugs based on the society in sukoharjo regency :2) to know and analyze the problems that faced by P4GN team in the prevention of the eradication of using and illit traffic of the drugs based on the society in sukoharjo regency. This research use the empiricial juridical method. thedata sources are get by the informant of event activities also the documents. The sampling techniq that used is purpose sampling. The technique of data collection that used to get and arrange the research datas are interview, observation, also analyze the document. Based on the result of this research, can conclude that : 1)the strategy and implementation the P4GN team in the prevention of the eradiction ofusing and illitic traffic of the drugs based on the society in sukoharjo regency. These are a) preventive program extention to 1000 suburb 2 nd step,b) goes to junior high school, senior high scholl and campus,c)bmonthly action program ,d) meet up program and mmet up community ,e)formating the education cadre, f)branding soft rehabilitation and the implementation with the concept that always change each year by adjusting the early condition that follow the growth in society. So can know the danger of the drugs that more threa tening this nation, next the society consiously declare the suburb without drugs as one of the rejection action to the drugs. 2)the problems that faced the strategy of p4gn team in the prevention of the eradiction and the illitic traffic based on the society in sukoharjo regency, such as : a) not yet formed the BNN in district level, b)the limitted of budget funds, c) the lack of human resources, d) the limitted of office facility,e) the society has not understand about P4GN Keywords : Strategy, P4GN Team, Drugs, Society.